Responses of belowground bud bank to disturbance and stress in the sand dune ecosystem. (November 2019) - Ma, Qun; Qian, Jianqiang; Tian, Liang; Liu, Zhimin
Graphical abstract: Highlights: Plants from habitats with intermediate disturbance and stress levels produce more buds than in other habitats. Root-sprouting buds were more adaptive to the severe wind-erosion prone habitats and water stress habitats. Tiller buds were predominant in sand burial disturbance-prone habitats and under lower stress magnitude. Rhizome buds were more sensitive to water stress and adaptive to low levels of disturbance and stress. Abstract: Exploring the role of belowground bud bank in plant adaptive strategies is essential for understanding the processes of vegetation regeneration under conditions of environmental disturbance and stress. Up to present, few studies have examined the response of bud bank size and composition to environmental stress and disturbance in sand dune environments. Here, three sand dune types (mobile, semi-fixed and fixed sand dunes), five dune positions (two characterized by severe, one by moderate and two by light water stress conditions), and two dune aspects (wind-erosion dune aspect and sand-burial dune aspect) were selected to test the hypothesis that aeolian activity disturbance and water stress play different roles in shaping the distribution of different bud bank types. One-way ANOVA and linear mixed effect models were applied to analyze the effect of dune type, position and aspect on bud bank density. We assessed how aeolian disturbance and water stress affect the regeneration capacity of bud bank in sand dunes. Our results showed that root-sprouting buds accounted for a larger proportion of the total number of buds in the windward aspect of the dunes, whereas tiller buds were predominant in the leeward aspect of the dunes. Plants tended to produce more rhizome buds and root collar buds in the lowland. Therefore our study indicated that root-sprouting buds are more important in habitats with severe wind erosion disturbance, whereas tiller buds are more important in the case of intensive sand burial disturbance; additionally, rhizome buds are proved more sensitive to water stress. The survival strategies and phenotypic responses observed here can be used to analyze indicators of population regeneration and should be carefully considered in sand dune management.